Association of genetic variants in six candidate genes with valproic acid therapy optimization. (August 2011) - Hung, Chin-Chuan; Ho, Jia-Ling; Chang, Wei-Lun; Tai, John Jen; Hsieh, Tsung-Jen; Hsieh, Yow-Wen; Liou, Horng-Huei
Aims: Valproic acid (VPA) is one of the most widely used antiepileptic drugs. The aim of the study was to investigate whether polymorphisms in genes related to pharmacokinetic and pharmacodynamic pathways of VPA were associated with the large interindividual variability in dosages and concentrations.Methods & results: Genetic polymorphisms in six candidate genes were detected in 162 epileptic patients under maintenance with VPA monotherapy and stable seizure control by real-time PCR and PCR-RFLP. Results of statistical analysis demonstrated that carriers of the variant UGT1A6 19T>G, 541A>G and 552A>C allele tended to require higher VPA dosages and lower ln(concentration-to-dose ratios [CDRs]) than noncarriers (p < 0.0001) and the homozygous carriers also seemed to require higher VPA dosages and lower lnCDRs (p < 0.0001). On the other hand, carriers of the variant GRIN2B -200T>G allele were more likely to require lower VPA dosages than noncarriers (p < 0.0001) and the homozygous carriers also tended to require lower dosages and higher lnCDRs (p < 0.0001). In addition, the regression model of CDR of VPA also revealed that genetic variants in UGT1A6, GRIN2B and UGT2B7 genes interactively affect CDRs of VPA (adjusted r 2 = 47%).Conclusion: Although there was a limited sample size, the study identified genetic factors associated with VPA therapy optimization that has not been revealed, and provided useful information for individualized VPA therapy in epileptic patients. Original submitted 9 February 2011; Revision submitted 20 April 2011